2013
DOI: 10.2217/fmb.13.31
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fosfomycin Activity Against Uropathogens in a Fosfomycin-Naive Population in South India: a Prospective Study

Abstract: Fosfomycin exhibits good in vitro activity against both the uropathogens tested. Therefore, it might be considered as a treatment option for urinary tract infections in India; however, clinical trials should first reinforce the in vitro findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 19 publications
3
12
2
1
Order By: Relevance
“…This rate is even higher than reported in some other developing countries (60−70%) (2, 5, 13, 22). By contrast, the prevalence of ESBL-producing isolates among Enterobacteriaceae in developed nations is much lower:<1% in Sweden (23) and 1.7% in France (24).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This rate is even higher than reported in some other developing countries (60−70%) (2, 5, 13, 22). By contrast, the prevalence of ESBL-producing isolates among Enterobacteriaceae in developed nations is much lower:<1% in Sweden (23) and 1.7% in France (24).…”
Section: Discussioncontrasting
confidence: 55%
“…Previous study showed that the most prevalent microorganism was E. coli , followed by K. pneumonia , and other Enterobacteriaceae (5, 6, 21, 27). A study from France in 2008 reported that the most prevalent species were E. coli (48.5%), Enterobacter aerogenes (23.7%), and K. pneumoniae (14.8%) (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fosfomycin was reported to have a good activity on all UTI isolates in various studies [27,28]. In the present study, only one Enterococcus isolate was resistant to vancomycin and teicoplanin, but it was also resistant to fosfomycin.…”
Section: Discussioncontrasting
confidence: 43%
“…In a study from Southern part of India, Sahni RD and co-workers reported Fosfomycin susceptibility of 83 and 99% for E. coli and Enterococcus spp, respectively. Among these, 81% of extendedspectrum β-lactamase producing E.coli was susceptible to fosfomycin, while 75.7% of multidrug resistant were found to be susceptible to fosfomycin [20].…”
Section: Resultsmentioning
confidence: 99%